Financial institutions efficiency: a systematic literature review - Danijel Petrović; Goran Karanović (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
This study conducts a systematic literature review on the effect of risk management on financial institutions’ efficiency. Using the PRISMA method, we analysed 173 studies published between 1990 and 2023 in journals ranked by Academic Journal Guide, issued by the Chartered Association of Business Schools in 2021. The results reveal that both parametric (Stochastic Frontier Approach) and non-parametric (Data Envelopment Analysis) models are equally utilized in estimating the efficiency of financial institutions. The limitations of these methodologies are discussed, while also indicating a lack of consensus on the classification of variables. Furthermore, the results show that recent studies mainly focus on the effects of mergers and acquisitions activities, regulation, and risk management on the efficiency of banks and insurance companies. Finally, a current trend towards developing composite indices in efficiency estimation is emphasized. Findings from this study will be useful to academics, researchers, financial institution managers, policymakers, and regulators interested in financial institutions’ efficiency.